A Method for Combining Classical and Deep Machine Learning for Mobile Health and Behavior Monitoring - Gjoreski, Martin (Informatica, 2021)
This paper summarizes the doctoral dissertation of the author, which presents a method for fusing classical and deep machine learning for mobile health and behavior monitoring with wearable sensors.